2012
DOI: 10.7314/apjcp.2012.13.10.4897
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mirtazapine on MNNG-Induced Gastric Adenocarcinoma in Rats

Abstract: Objective: In this study, anticancer effects of mirtazapine on rats were investigated in an adenocarcinoma model induced by N-methyl-N-nitro-N-nitrosoguanidine (MNNG) and compared with those of cisplatin. Materials and Methods: For this purpose, 10 mg/kg doses of mirtazapine were administered orally to one group of rats, while 1 mg/kg doses of cisplatin were administered intraperitoneally to another group. At 1 hour after administration, 200 mg/kg doses of MNNG were given orally to both groups. MNNG administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A record linkage from Finland utilizing nationwide databases did not identify any association between antidepressant exposure and incident gastric carcinoma[ 16 ]. Moreover, experimental data reported that mirtazapine prevented adenocarcinoma induction by N-methyl-N-nitro-N-nitrosoguanidine (MNNG) in rats to a greater extent than cisplatin[ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A record linkage from Finland utilizing nationwide databases did not identify any association between antidepressant exposure and incident gastric carcinoma[ 16 ]. Moreover, experimental data reported that mirtazapine prevented adenocarcinoma induction by N-methyl-N-nitro-N-nitrosoguanidine (MNNG) in rats to a greater extent than cisplatin[ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer (GC) is the fourth most common cancer and causes almost one million deaths one year worldwide (Toyoda et al 2013). Helicobacter pylori infection, lifestyle (including high-salt diet and smoking), obesity, radiation exposure, Epstein-Barr virus infection, and environmental factors increase GC risk (Bilici et al 2012;Menheniott et al 2016). GC initiates with chronic gastritis to gastric atrophy, intestinal metaplasia, dysplasia, and finally to adenocarcinoma (Menheniott et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The success of several recent clinical trials in terms of cancer prevention among high-risk populations suggests that chemoprevention is a rational and effective strategy (Tsao et al, 2004). Chemoprevention has received considerable attention as a potential means to control the incidence of gastric cancer (Ganapathy et al, 2008;Lu et al, 2008;Xu et al, 2011;Bilici et al, 2012).…”
Section: Preventive Effect Of Actinidia Valvatamentioning
confidence: 99%